SiO2 nanosphere coated tough catheter with superhydrophobic surface for improving the antibacteria and hemocompatibility - Zhang, Weixing; Du, Juan; Zhu, Tonghe; Wang, Ruilan (Frontiers in Bioengineering and Biotechnology, 2023)
Catheter infection is the most common complication after vascular catheter placement, which seriously threatens the survival of critically ill patients. Although catheters with antibacterial drug coatings have been used, catheter infections have not been effectively resolved. In this research, a SiO2 nanosphere-coated PTFE catheter (PTFE-SiO2) with enhanced antibacterial and excellent mechanical properties was prepared via dopamine as a graft bridge. The microscopic morphology results show that the nanospheres are uniformly dispersed on the surface of the catheter. The physicochemical characterization confirmed that PTFE-SiO2 had reliable bending resistance properties, superhydrophobicity, and cytocompatibility and could inhibit thrombosis. Antibacterial results revealed that PTFE-SiO2 could hinder the reproduction of E. coli and S. aureus. This research demonstrates the hydroxyl-rich materials obtained by hydroboration oxidation have the advantages of better dispersion of functional coatings, indicating their potential for helpful modification of catheters.